Pentingnya Human Relations Dalam Membangun Kualitas Komunikasi di Organisasi Kampus - Maulana Yusuf; Leo Feni Agustina; Nessya Mayla; Nazlah Azzahra; April Laksana (STIKes Ibnu Sina Ajibarang, 2025)
Every organization must have problems, problems that often arise in organizations are disharmonious relationships between leaders and their members, or between fellow members. This problem is caused by interference barriers in organizational communication. All organizational activities will run in accordance with their respective duties and functions if communication takes place effectively in all lines of the organization. Conversely, failure to foster effective and harmonious communication will hamper the implementation of tasks in the organization. Without communication there is no coordination, and without coordination there will be overlapping work, confusion of information, and misunderstanding in interpreting and carrying out organizational tasks. Organizational leaders are the spearhead of the organization to create comfort, bring motivation, and foster loyalty to the organization. every organization must apply the principles of public relations and human relations in order to build effective communication quality.